2014
DOI: 10.1111/psyp.12246
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of cardiac vagal control in 24‐h heart rate variability recordings: Influence of ceiling effects at low heart rates

Abstract: This study estimated the heritability of 24-h heart rate variability (HRV) measures, while considering ceiling effects on HRV at low heart rates during the night. HRV was indexed by the standard deviation of all valid interbeat intervals (SDNN), the root mean square of differences between valid, successive interbeat intervals (RMSSD), and peak-valley respiratory sinus arrhythmia (pvRSA). Sleep and waking levels of cardiac vagal control were assessed in 1,003 twins and 285 of their non-twin siblings. Comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 114 publications
1
27
0
Order By: Relevance
“…However, the genetic factors influencing individual differences in resting versus stress‐response HR appear to be distinct [Ditto, ; Wu et al, ]. HRV is also moderately heritable, with estimates from four studies at around 50% [Riese et al, ; Wang et al, ; Su et al, ; Neijts et al, ], although heritability varied for different types of measures such as high versus low frequency spectral power. Unlike HR, 60–81% of the latent genetic influences were shared between resting and stress‐response HRV [Wang et al, ], possibly because variation in heart rate intrinsically reflects an organism's changing response to the immediate environment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the genetic factors influencing individual differences in resting versus stress‐response HR appear to be distinct [Ditto, ; Wu et al, ]. HRV is also moderately heritable, with estimates from four studies at around 50% [Riese et al, ; Wang et al, ; Su et al, ; Neijts et al, ], although heritability varied for different types of measures such as high versus low frequency spectral power. Unlike HR, 60–81% of the latent genetic influences were shared between resting and stress‐response HRV [Wang et al, ], possibly because variation in heart rate intrinsically reflects an organism's changing response to the immediate environment.…”
Section: Resultsmentioning
confidence: 99%
“…Time domain measures of HRV showed heritability in a similar range (35–48%) (Kupper et al, 2004). Another twin study of time domain HRV measures based on 24-h ambulatory recordings yielded significant heritabilities of time domain variables ranging from46 to 57% and indicated a substantial overlap of genetic influences on two time domain HRV measures, standard deviation of the R-R intervals (SDNN) and the RMSSD (Neijts et al, 2014). A study using a nonlinear dynamical measure of HRV (approximate entropy) showed only a modest heritability of 40% (Snieder et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise resting RSA is substantially heritable with estimates ranging between 25 and 71 % (de Geus et al 2015; Neijts et al 2014). We replicate these findings in our sample (heart rate 68 %, RSA 58 %) with the heritability of resting heart rate very similar to a recent meta-analysis done by Wang et al (Wang et al 2015) and the heritability of resting RSA very similar to that found in a large non-overlapping study in adult Dutch twins (50 %) (Neijts et al 2015).…”
Section: Discussionmentioning
confidence: 99%